(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
Reports a diverse microflora from the Late Viséan Opal Member, Fernie, Rocky Mountains, Canada. A shallow-water limestone level yields forty identifiable taxa of green and red algae associated with microproblematica. Four species are new : Cabrieropora opalae, Cribrokamaena ferniensis, Koninckopora pachytheca and Moravammina ? enigmatica. Inferred sedimentation is open marine, in normal salinity, from the middle part of the euphotic zone, within the fair-weather wave zone. A semi-restricted lagoon located nearby provides floated calcispheres. The high diversity is due to the excellent preservation of the thalli which were protected by a thin early coating of bacterial micrite.